Obesity, hunger, and agriculture: the damaging role of subsidies - Elinder, Liselotte Schäfer (BMJ Publishing Group Ltd., 2005)
Globally, we are producing more food than the population needs. Subsidising overproduction in Europe is affecting the health of people in both Africa and Europe